Homogeneous boiling over melting ice - Ty Hagan; Ahmad Vasel-Be-Hagh (Scientific Reports)
Abstract We report on discovering the homogeneous boiling within a liquid film residual resting in equilibrium over a melting ice block. This phenomenon was induced via longwave infrared radiation generated by a continuous wave $$\hbox {CO}_2$$ laser. This investigation employed a high-speed camera and the Schlieren visualization technique. The study discovered that the presence of ice substantially lowered the minimum power intensity required for homogeneous nucleation to occur. This observation is counterintuitive, as one might intuitively believe ice presence would result in enhanced cooling, demanding a higher power to initiate boiling. We offer three reasons for this observation: (1) the suppression of convective dissipation of the heat via the ice below the melted water, (2) instabilities caused by substantial temperature gradients between the irradiated meltwater and ice surface, and (3) instabilities caused by pressure gradients due to uneven melting of the ice surface. The effect of impurities was also tested by adding borax to the ice. Borated ice exhibited homogeneous and heterogeneous boiling simultaneously, demonstrating an even lower power intensity to initiate thermocavitation.